2019
DOI: 10.1136/gutjnl-2018-316772
|View full text |Cite
|
Sign up to set email alerts
|

Non-classical monocyte homing to the gut via α4β7 integrin mediates macrophage-dependent intestinal wound healing

Abstract: ObjectiveTo study the role of α4β7 integrin for gut homing of monocytes and to explore the biological consequences of therapeutic α4β7 inhibition with regard to intestinal wound healing.DesignWe studied the expression of homing markers on monocyte subsets in the peripheral blood and on macrophage subsets in the gut of patients with IBD and controls with flow cytometry and immunohistochemistry. Integrin function was addressed with dynamic adhesion assays and in vivo gut homing assays. In vivo wound healing was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 53 publications
8
86
1
Order By: Relevance
“…We read with interest the recent work by Schleier et al 1 demonstrating consequences of impaired α4β7 integrin-dependent gut homing of intestinal macrophages on wound healing, which fits well with own observations we have made in a case of congenital infantile intractable diarrhoea linked to impaired integrin receptors in intestinal epithelia (α V β6). Specifically, a male dizygotic twin was delivered dystrophic (1715 g) at 36 weeks of gestational age and developed intractable diarrhoea within the following 2 months, contrary to his twin brother.…”
supporting
confidence: 87%
“…We read with interest the recent work by Schleier et al 1 demonstrating consequences of impaired α4β7 integrin-dependent gut homing of intestinal macrophages on wound healing, which fits well with own observations we have made in a case of congenital infantile intractable diarrhoea linked to impaired integrin receptors in intestinal epithelia (α V β6). Specifically, a male dizygotic twin was delivered dystrophic (1715 g) at 36 weeks of gestational age and developed intractable diarrhoea within the following 2 months, contrary to his twin brother.…”
supporting
confidence: 87%
“…It prevents lymphocyte infiltration from the blood into the inflamed gut tissue, reducing local inflammation [51]. In addition to this effect, vedolizumab also reduces α4β7-dependent gut homing of non-classical monocytes, resulting in a decrease in alternatively activated M2-like macrophages in the gut [52]. In contrast to other anti-adhesion drugs, the use of vedolizumab in UC patients did not increase the rates of opportunistic or enteric infections and there were no reported cases of progressive multifocal leukoencephalopathy [53].…”
Section: The Role Of Biomarkers and Treatment Options In Ucmentioning
confidence: 99%
“…Following encouraging results in randomized, double-blind, placebo-controlled trials in the pivotal phase III GEMINI studies, vedolizumab has been approved by US FDA for the treatment of adult patients with active UC who had a poor response to standard therapies [54]. Nevertheless, mononuclear phagocyte enrichment was detected in non-responder UC patients before vedolizumab treatment, which further increased post treatment [52], partly explaining why some UC patients do not respond as well to this drug.…”
Section: The Role Of Biomarkers and Treatment Options In Ucmentioning
confidence: 99%
“…The anti-α4β7 antibody vedolizumab is successfully used for the treatment of IBD since 2014 [3,8] and has been shown to inhibit immune cell homing to the inflamed gut [9,10] indicating that cell trafficking is a central event in the pathogenesis of IBD [11]. Randomized controlled trials [3,8], as well as several real-world cohorts [12][13][14], demonstrated the efficacy and safety of vedolizumab in ulcerative colitis (UC) and Crohn's disease (CD).…”
Section: Introductionmentioning
confidence: 99%